Impact of Anxiety and Personality on Speaking Performance of Public Senior Secondary School - Alyarosali Alyarosali; Maemuna Muhayyang; Munir Munir (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2023)
This study aims to find out the anxiety has an impact on speaking performance, to find out personality has an impact on speaking performance, and to find out students’ strategies to reduce anxiety in speaking performance. This research took place at SMA Negeri 3 Makassar. The population of this research was the second-grade students of SMA Negeri 3 Makassar. The researchers used convergent parallel. This research uses quantitative and qualitative design. The sample of the questionnaire is 30 students and Interviews with 5 students were taken using a purposive sampling technique. There are four students had high-level anxiety (13,3%), ten students had medium-level anxiety (33,3%), and sixteen students had low-level anxiety (53,3%). (2) students’ explanations in interviews regarding strategies to reduce their anxiety have several strategies that they do such as preparation, relaxation, positive thinking, resignation, and looking away. The researchers can conclude that different levels of anxiety and personality can have an impact on speaking performance. But students at SMA Negeri 3 Makassar have a good strategy to reduce their anxiety when speaking performance.